Black Holes and Revelations: Michel Henry and Jean-Luc Marion on the Aesthetics of the Invisible - Fritz, Peter Joseph (Modern theology, 2009)
This essay examines how Michel Henry's and Jean-Luc Marion's continuation of phenomenology's turn to the invisible relates to painting, aesthetics, and theology. First, it discusses Henry and Marion's redefinition of phenomenality. Second, it explores Henry's "Kandinskian" description of abstract painting as expressing "Life." Third, it explicates Marion's "Rothkoian" rehabilitation of the idol and renewed zeal for the icon—both phenomena exemplify "givenness." Fourth, it unpacks my thesis: Henry's phenomenology, theologically applied, exercises an inadequate Kantian apophasis, characterized by a sublime sacrifice of the imagination; although Marion's work sometimes evidences a similar tendency, its prevailing momentum offers theology a fully catholic scope.